Effect of Heparin on the Activation of Factor XI by Fibrin-bound Thrombin - von dem Borne, Peter A Kr; Meijers, Joost C M; Bouma, Bonno N (Thrombosis and Haemostasis, 1996)
Fibrin-bound thrombin is protected from inactivation by antithrombin III, while its coagulant potential is retained. In the presence of heparin, ternary complexes between thrombin, fibrin and heparin are formed. In these complexes the coagulant activity of thrombin is retained, whereas the anticoagulant activity of fibrin-bound heparin is neutralized. The limited effectiveness of heparin in the prevention of both venous thrombosis and coronary reocclusion is probably related to the protective effect of fibrin on the inactivation of thrombin by antithrombin III. Recently, it has been shown that factor XI can be activated by thrombin, resulting in the generation of additional thrombin via the intrinsic pathway. This additional thrombin is capable of stabilizing the clot by protecting it from fibrinolysis. We studied the effect of heparin on the activation of factor XI by fibrin-bound thrombin. First, we used fibrin monomers coupled to Sepharose to which thrombin and unfractionated heparin (UFH) were bound. Factor XI activation by thrombin was the same in the presence of fibrin-Sepharose or control-Sepha-rose. The addition of heparin (0.1 U/ml) resulted in a 91 and 15-fold enhancement in the presence of control-Sepharose and fibrin-Sepharose, respectively. Next, we added complexes of heparin, thrombin and fibrin monomer to factor XII and XI double-deficient plasma in the presence or absence of a reconstituting amount of factor XI. In the presence of factor XI, additional fibrin formation was observed indicating that factor XI activation by thrombin in complex with fibrin and heparin can take place in plasma. We then studied the effect of other heparin-like anticoagulants on the thrombin-mediated factor XI activation. UFH enhanced thrombin-mediated factor XI activation 68-fold, LMWH (low molecular weight heparin, Fragmin) 12-fold, danaparoid (Orgaran) 3-fold, while the pentasaccharide ORG 31540 did not result in an enhancement. Binding studies of these anticoagulants to fibrin-Sepharose showed that LMWH bound with approximately the same affinity as UFH, while danaparoid and the pentasaccharide did not bind to fibrin.We conclude that fibrin-bound thrombin is capable of factor XI activation. Furthermore, heparin bound in a complex with fibrin can act as a cofactor for this activation. This factor XI activation capacity may play a role in the limited effectiveness of heparin. Provided that thrombin-mediated factor XI activation plays an important role in vivo, danaparoid and especially the pentasaccharide may be better anticoagulants than UFH and LMWH.